2013
DOI: 10.2478/eko-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Ecological Factor S Affecting Environmental Function S of the Soil S in Area of Traditional Agrarian Structure S

Abstract: Krnačova Z., Hreško J., Kanka R., Boltižiar M.: The evaluation of ecological factors affecting environmental functions of the soils in area of traditional agrarian structure. Ekologia (Bratislava),Vol. 32, No. 2, p. 248-261, 2013. Cultural landscape can be seen as a result of hundred years of founding and sensitive cultivation of landscape structures respecting natural conditions. Specific geomorphological, climatic as well as social conditions enabled the conservation of original agrarian landscape structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Content of P 2 O 5 ranged from 10.41 to > 40%; content of N ranged from 0.11 to 0.23%; content K 2 O ranges from 9.76 to > 40%; the humus content ranged from 2.38 to 3.81%; the pH value ranged from 4.28 to 6.23. The results obtained for the pH in the soil samples coincide with the pH values obtained in Bratislava where similar soil tests were performed (pH/KCl 4.81-5.21) (Krnacova et al, 2013).…”
Section: Resultssupporting
confidence: 83%
“…Content of P 2 O 5 ranged from 10.41 to > 40%; content of N ranged from 0.11 to 0.23%; content K 2 O ranges from 9.76 to > 40%; the humus content ranged from 2.38 to 3.81%; the pH value ranged from 4.28 to 6.23. The results obtained for the pH in the soil samples coincide with the pH values obtained in Bratislava where similar soil tests were performed (pH/KCl 4.81-5.21) (Krnacova et al, 2013).…”
Section: Resultssupporting
confidence: 83%
“…In Slovakia, changes in cultural and agricultural landscape were studied by Cebecauerová (2007), Boltižiar and Chrastina (2008), Blažík et al (2011), Muchová et al (2010, Ivanová et al (2013), Krnáčová et al, (2013), Tarasovičová et al (2013), Kopecká, Rosina (2014) Lieskovský et al 2014 andŠebo, Kopecká (2014). This paper deals with the classification of land use changes and it investigates changes in Nitra town during the period 2003−2013.…”
Section: Introductionmentioning
confidence: 99%
“…Even if nitrophilous species occur in mosaics with arable fields, their proportion was not very high, reflecting the semi-natural character of these traditional agricultural structures developed over the centuries. Other studies found that traditional extensive maintenance of the agricultural landscape help to maintain biological and genetic diversity in these ecosystems (Altieri and Merrick 1987) and preserve optimal environmental characteristics of soils (Krnáčová et al 2013).…”
Section: Connecting Ecological and Cultural-historical Diversitymentioning
confidence: 99%